Architecture in National Identities: a critical review. Issue 4 (7th August 2020) - Pandya, Samir
ABSTRACT: This review article reflects on a representative sample of past architecture submissions to the journal National Identities: Critical Inquiry into Nationhood, Politics & Culture . The articles reviewed are drawn from those published since the inaugural issue through to date, spanning a period of twenty-one years. Twenty-four articles (of thirty-five initially reviewed) are included and organised into three categories: Typology, Remembrance and Geopolitics. Thematic, conceptual and analytical distinctions and commonalities between articles are highlighted, with the aim of providing an overview of the scholarship and intellectual territory covered. Beyond the particular categories identified, the article identifies the problem of form and context as central to any research interest in architectural nationalism, and suggests future lines of inquiry that may also provide generalisable benefits for the advancement of the discipline more broadly.